Comparison of Print Modules and E-Modules to the Tolerance Character of Students - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Damayanti, Latipia (Universitas Pendidikan Ganesha, 2021)
The purpose of this study was to determine the tolerance character indicators through the application of two learning modules. This type of research is quantitative research, this study involves two variables, namely learning teaching materials in class with a sample size of 32 students. Data analysis used descriptive and inferential statistics. The character of students' social care can be seen in the application of the electronic module and the print module. The result, from the two teaching materials, the tolerance character of the fifth grade students of SD 45 / I Sridadi was dominant in the good category when implementing the electronic module, while the tolerance character of the students with the application of the printed module was dominant in the sufficient category.